Combined Acupuncture and Shirodhara as an Effective Treatment Approach in the Management of Progressive Bulbar Palsy: A Case Report - Satyal, Jaya; KC, Pradeep; KC, Rachana; Sharma, Aabha; Chandra, Avinash (Annapurna Journal of Health Sciences, 2023)
Progressive bulbar palsy is a motor neuron disease with symptoms of dysarthria, dysphagia, sialorrhea with tongue muscle atrophy and fasciculation. A patient came to a tertiary neurological center with symptoms of dysphagia, dysarthria and excessive salivation from last 6 months. Patient stated that the several medications were tried including Tab. Riluzole and injection edaravone without any success. Hence the integrated approach of western and Eastern alternative therapy including Acupuncture and Ayurveda Shirodhara was started for 18 days. Patient was initially assessed via Dysphagia Score and NIH Dysarthria score before the commencement of the treatment session. This case demonstrates that the acupuncture and shirodhara can be an effective treatment approach for the management of progressive bulbar palsy.